2017
DOI: 10.1039/c7ra07859e
|View full text |Cite
|
Sign up to set email alerts
|

Doping-template approach of porous-walled graphitic nanocages for superior performance anodes of lithium ion batteries

Abstract: Removal of the N-doped template creates nanopores in the shells of nanocages. The created nanopores enhance fast ion diffusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…As the comparison, interfacial lithium-ion transfer reaction at the interface between GCNS electrode and organic electrolyte solutions were investigated beforehand. In addition, the effect of the structural difference of CNSs prepared at different temperature for interfacial lithium/sodium-ion transfer reaction was also investigated because the defects in the graphitic materials [21,22] and the gaps between graphene layers inside graphitic materials [23,24] influence the diffusion of lithium/sodium-ion. Our group previously reported that the sodium-ion insertion and diffusion inside CNSs seemed to be promoted using CNSs treated at low temperature due to the defects and large interlayer distances [8].…”
Section: Introductionmentioning
confidence: 99%
“…As the comparison, interfacial lithium-ion transfer reaction at the interface between GCNS electrode and organic electrolyte solutions were investigated beforehand. In addition, the effect of the structural difference of CNSs prepared at different temperature for interfacial lithium/sodium-ion transfer reaction was also investigated because the defects in the graphitic materials [21,22] and the gaps between graphene layers inside graphitic materials [23,24] influence the diffusion of lithium/sodium-ion. Our group previously reported that the sodium-ion insertion and diffusion inside CNSs seemed to be promoted using CNSs treated at low temperature due to the defects and large interlayer distances [8].…”
Section: Introductionmentioning
confidence: 99%
“…15,16 In recent years, many studies have investigated methods to overcome the above defects: one strategy is loading these active materials on a conductive framework (such as graphene, porous carbon, amorphous carbon) to enhance the transfer of electrodes; [17][18][19][20][21] the preparation of an active materials@shell structure is another strategy to buffer the excessive volume effect as the strong skeleton of shells limits the volume change of active materials in charge/ discharge processes. 8,[22][23][24][25][26][27] Additionally, modifying the structure of electrodes is also an efficient strategy to conquer the above challenges. [28][29][30][31][32] Fe 3 O 4 /Cu nanorod anodes were fabricated by a two-step approach: Cu nanorods were grown using a electrochemically assisted template method and then Fe 3 O 4 nanoparticles were electrodeposited.…”
Section: Introductionmentioning
confidence: 99%